Selection of Sap Well Trees by a Keystone Species : the Red-Naped Sapsucker (Sphyrapicus Nuchalis) - Ames, Jon (My University, 2012)
Conserving keystone species requires understanding their feeding requirements. One of the most important keystone species is the Red-naped Sapsucker, a woodpecker that excavates its nest holes in aspens and drills sap wells in aspens and other trees/shrubs. This study investigated the criteria used by sapsuckers in their choice of sap well trees in aspen woodlands of the Rocky Mountains.
Color poster with text, photographs, maps, and graphs.
Keywords: Aspen; Red-naped sapsucker; Woodpeckers--Habitat; Posters